The effeciancy of memorizing piano piece in helping piano students to perform in Faculty of Music, UiTM Shah Alam / Amira Eva Sherin Roslan - Roslan, Amira Eva Sherin (Faculty of Music, 2016)
Musicians are expected to perform by memory. Society and audience within certain musical genre believes that performing with notated sheet musu are unbelievable (Ginsborg, 2004) This also applies for pianists. Tomassini (1999) stated that it is to be expected that all recital for solo piano is to be performed from memory except for contemporary music. It seems to be the general consensus for pianist is to perform by memory. Although it is general for musicians to perform music by memory, it is still extremely hard for the performers to do so. Williamon (2002) stated that before performers have to perform by memory in a stressful situation, performers had to start with memorizing the music piece which consists of complex musical structure and the notes…